Operando Radiography and Multimodal Analysis of Lithium–Sulfur Pouch Cells—Electrolyte Dependent Morphology Evolution at the Cathode. Issue 13 (18th February 2022) - Müller, Rafael; Manke, Ingo; Hilger, André; Kardjilov, Nikolay; Boenke, Tom; Reuter, Florian; Dörfler, Susanne; Abendroth, Thomas; Härtel, Paul; Althues, Holger; Kaskel, Stefan; Risse, Sebastian
Abstract: In recent years, the technology readiness level of next‐generation lithium–sulfur (Li/S) batteries has shifted from coin cell to pouch cell dimensions. Promising optimizations of the electrodes, electrolytes, active materials, and additives lead to improved performance and cycling stability. However, new challenges arise with the pouch cell design and engineering (including electrode stacking and electrolyte filling), which influence the mechanistic processes of the cell. This study presents an unprecedented multimodal operando investigation of Li/S batteries on a pouch cell level and provides an inside view of material transformations during battery cycling, using X‐ray radiography, electrochemical impedance spectroscopy, and spatially resolved temperature monitoring. With the comparison of two different electrolytes, new experimental details about sulfur and lithium sulfide deposition and dissolution processes are revealed and related to electrolyte and temperature distribution. Operando impedance measurements on monolayer pouch cells yield a clear correlation of electrochemical and macroscopic radiographic observations. Understanding the monolayer cells' behavior represents an optimal foundation for further studies on multilayer pouch cell prototypes and demonstrators with the developed operando setup. Herein the proof of principle for correlated measurement methods on pouch cell level is shown, and the experimental proof of concept for sulfur crystal suppression in sparingly solvating electrolyte is visualized. Abstract : Lithium–sulfur pouch cells are analyzed while charging and discharging. X‐ray imaging provides insight into cell materials and phase transformations. Two different electrolytes are compared, and the effect of the sparingly solvating electrolyte is evaluated. Inhomogeneous electrode activity is observed, and correlations to voltage curves and temperature profiles are established.